2013
DOI: 10.1098/rstb.2013.0020
|View full text |Cite
|
Sign up to set email alerts
|

Deep conservation ofcis-regulatory elements in metazoans

Abstract: Despite the vast morphological variation observed across phyla, animals share multiple basic developmental processes orchestrated by a common ancestral gene toolkit. These genes interact with each other building complex gene regulatory networks (GRNs), which are encoded in the genome by cis -regulatory elements (CREs) that serve as computational units of the network. Although GRN subcircuits involved in ancient developmental processes are expected to be at least partially conserved, ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 122 publications
(189 reference statements)
0
22
0
Order By: Relevance
“…they contain the same collection of TF recognition motifs, although located at different positions within the DHS) and in many cases, they also maintain the same tissue specific activities [6]. Similar to this latter case, two studies comparing orthologous regulatory landscapes in different insect species have shown that functionally equivalent enhancers are maintained at equivalent genomic positions, even though their underlying sequences have diverged beyond recognition [83,84], as it has been discussed elsewhere [15,85].…”
Section: Permissive Genomic Environments For Enhancer Evolution At Thmentioning
confidence: 76%
See 1 more Smart Citation
“…they contain the same collection of TF recognition motifs, although located at different positions within the DHS) and in many cases, they also maintain the same tissue specific activities [6]. Similar to this latter case, two studies comparing orthologous regulatory landscapes in different insect species have shown that functionally equivalent enhancers are maintained at equivalent genomic positions, even though their underlying sequences have diverged beyond recognition [83,84], as it has been discussed elsewhere [15,85].…”
Section: Permissive Genomic Environments For Enhancer Evolution At Thmentioning
confidence: 76%
“…Furthermore, the distribution of functional elements in the genome, and of CREs in particular, is far from being uniform. Highly distinctive features demarcate the genes and genomic regions around developmental genes, with much larger intergenic distances, longer and more numerous introns and higher evolutionary constraint, both in terms of sequence and synteny conservation [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Deep regulatory homologies, at distances where genomes have diverged too far to make use of sequence alignment—even trans-phyletically—have been reported previously [47, 52], but the challenges inherent in identifying homologous CRMs have kept examples to a minimum (see Outstanding Questions). Furthermore, conservation of function does not always mean conservation of mechanism.…”
Section: Concluding Remarks: An Exciting Time For Studies Of Grn Evolmentioning
confidence: 99%
“…Latest evidences are highlighting that divergence in cis -regulatory sequences might underlie phenotypic diversity in evolution more commonly than divergence in the sequences of the TFs themselves. Gain, loss or changes in the affinity of TFs at the level of REs can indeed shape gene regulatory networks [ 1 ] [ 2 ]. In addition, co-evolution of cis -regulatory elements and of TF proteins is emerging as an extremely important evolutionary process, defined as cis-trans co-evolution [ 3 ].…”
Section: Introductionmentioning
confidence: 99%